Effect of niche components on masseter satellite cell differentiation on fibrin coatings. (12th January 2022) - Lijten, Olivier Willem; Rosero Salazar, Doris Haydee; van Erp, Merijn; Bronkhorst, Ewald; Von den Hoff, Johannes W.
Abstract: In skeletal muscles, niche factors stimulate satellite cells to activate and induce muscle regeneration after injury. In vitro, matrigel is widely used for myoblast differentiation, however, is unsuitable for clinical applications. Therefore, this study aimed to analyze attachment and differentiation of satellite cells into myotubes on fibrin coatings with selected niche components. The attachment of satellite cells to fibrin alone and fibrin with niche components (laminin, collagen‐IV, laminin‐entactin complex [LEC]) were compared to matrigel. Only on matrigel and fibrin with LEC, Pax7‐positive cells attached well. Then, LEC was selected to analyze proliferation, differentiation, and fusion indices. The proliferation index at day 1 on fibrin‐LEC (22.5%, SD 9.1%) was similar to that on matrigel (30.8% [SD 11.1%]). The differentiation index on fibrin‐LEC (28.7% [SD 6.1%] at day 5 and 32.8% [SD 6.7%] at day 7) was similar to that on matrigel (40.1% [5.1%] at day 5 and 27.1% [SD 4.3%] at day 7). On fibrin‐LEC, the fusion index at day 9 (26.9% [SD 11.5%]) was similar to that on matrigel (25.5% [SD 4.7%]). Our results showed that the addition of LEC enhances the formation of myotubes on fibrin. Fibrin with LEC might be suitable to enhance muscle regeneration after surgery such as cleft palate repair and other muscle defects.